Simultaneous Determination of Trace Amounts of Iron, Cobalt, Nickel and Chromium in Water Samples with Calcon as Complexing Agent by Adsorptive Stripping Voltammetry - Deswati; Munaf, Edison; Suyani, Hamzar; Zein, Rahmiana; Pardi, Hilfi (Asian Journal of Chemistry, 2015)
This paper presents a sensitive and selective method for simultaneous determination of iron, cobalt, nickel and chromium in water samples by adsorptive stripping voltammetry. The method is based on adsorptive accumulation of the complexes of Fe(III), Co(II), Ni(II) and Cr(III) ions with calcon [IUPAC name sodium-3-hydroxy-4[(E)(2-hydroxy-1-naphthyl)diazenyl]-1-naphthalenesulfonate (m.f. C20H13N2NaO5S] onto hanging mercury drop electrode (HMDE), followed by the reduction of the adsorbed species by differential pulse adsorptive stripping voltammetry. In this study the optimum reaction parameters and conditions study are investigated. Optimal conditions were obtained at pH 7.0, calcon concentration of 0.8 mM, the accumulation potential of -0.7 V and the accumulation time of 70 s. At the optimum conditions the relative standard deviation were 1.70, 2.40, 6.13 and 5.36 % for Fe(III), Co(II), Ni(II) and Cr(III), respectively for eight replicates (n = 8) measurements of 10 μg/L Fe(III), Co(II), Ni(II) and Cr(III). Under optimized conditions, linear calibration curves were established for the concentration of Fe(III), Co(II), Ni(II) and Cr(III) in the range 0.2-80.0; 0.2-120.0; 0.2-100.0 and 0.2-110.0 μg/L, respectively. The limit of detection of the method was 0.703 μg/L for Fe(III), 0.232 μg/L for Co(II), 0.974 μg/L for Ni(II) and 0.161 μg/L for Cr(III). The procedure was successfully applied to the simultaneous determination of iron(III), cobalt(II), nickel(II) and chromium(III) in water samples (sea water, tap water and river water) with recovery of 99.15, 103.73, 97.55 and 99.23 % for Fe(III), Co(II), Ni(II) and Cr(III) respectively.